(untitled) (Bangladesh Journal of Pharmacology, 2015)
Many plants contain active substances that are known to be effective in both enhancing the wound healing process and lowering the incidence of wound infections. Previous studies have shown that bryophytes produce a variety of secondary metabolites that present pharmaceutical activities including antimicrobial activity against various pathogenic bacteria and fungi. The aim of this study was to investigate the antimicrobial activity of Mnium stellare against 17 bacterial and 1 fungal strains. Our present study has shown that the ethanol extract of M. stellare has antimicrobial activity against several Gram positive and Gram negative microorganism tested, but its antimicrobial activity is notable especially against B. subtilis, S. typhimirium, S. aureus, S. carnosus, and S. epidermidis. These results are the very first report of the antimicrobial activity of M. stellare.